A Study on ESL Learners' Perceptions of Using One to One Online Support and Learning - Bareq Raad; Raashid Nehal (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
The present study aims to find the ESL learners' perceptions of the challenges of using online learning amidst covid-19. It also intends to find out their perceptions about the efficiency of using online classes to improve their English language soft skills. For this, the researchers have designed a survey incorporating two questionnaires using Five-point Likert scales. The first questionnaire is related to the challenges of online learning, and the second is connected to English language soft skills. They were distributed to 30 postgraduate ESL students from the department of English, Aligarh Muslim University (AMU). The findings reveal mixed perceptions (positive and negative). The subjects have shown positive perceptions regarding the challenges in online classes and doing assignments depending on online sources. They have also revealed positive perceptions about the interactive and proper discipline of the classroom in offline mode. In contrast, they have shown negative perceptions regarding comparing offline and online study modes and about the methodological challenges of learning in online classes and doing online assignments. In terms of improving their soft English skills, the subjects have shown positive perceptions regarding the efficiency of online classes in enhancing their reading, speaking and listening skills and negative perceptions regarding writing skills.